Validity and Reliability of the Persian Version of COVID-19 Anxiety Syndrome Scale Among the Iranian General Population - Hoseinzadeh, Esmaeil; Ebadi, Abbas; Sharif Nia, Hamid; Sivarajan Froelicher, Erika; Rahmatpour, Pardis (Frontiers in Public Health, 2022)
The COVID-19 anxiety syndrome scale assesses conceptually and psychometrically the nature of the COVID-19 threat experience instead of a response to the threat, fear, and COVID-19 anxiety. Therefore, the aim of study is to evaluate the psychometric properties of the Persian version of the anxiety syndrome scale of Covid-19 in the population of Iran. Iranian adults (n=932) responded the Persian version of C-19ASS that was sent via online social networking applications. The results of exploratory factor analysis revealed two-factor structures for C-19ASS, which explained 48.70% of the total variance. Given the confirmatory factor analysis findings, all goodness of fit indices confirmed the model fit. All coefficients of internal consistency were estimated as acceptable reliability. According to results, the C-19ASS has good psychometric properties. It could be used by researchers, psychologists, and healthcare providers to assess an anxiety syndrome of Iranian population during the COVID-19 pandemic.